Harmoni Bunyi di Kota Kuali - Adilla, Ivan (Universitas Andalas, 2024)
As a mining city, Sawahlunto was shaped by a variety of cultures. The city developed through the presence of workers from diverse cultural backgrounds. Over time, these different cultures interacted with one another. Through this process, some cultures coexisted harmoniously, while others merged to form new expressions as a result of acculturation. The arts, language, and way of life that emerged reflect the cultural processes that occurred. The cultural identity of Sawahlunto as a mining town exemplifies how the culture of mining or industrial communities is formed. This hybrid and heterogeneous identity holds intriguing cultural values, making it an interesting subject for further study to uncover insights into the process of cultural formation.